Exploring Teacher’s Cognition and Practices of Testing Speaking in Colombian Universities - Idarraga Robayo, Lorena (Colombian Applied Linguistics Journal, 2026)
This study examines Colombian English teachers’ knowledge, experiences, and views regarding speaking assessments. Semi-structured interviews were conducted with Colombian teachers, some of whom also shared classroom assessment samples. Thematic analysis was used for the interviews, and content analysis was applied to the assessment materials. Findings revealed a clear link between teachers’ perceptions of testing and their approach to presenting it to students. Furthermore, a correlation exists between their knowledge and experience in designing, administering, and evaluating speaking tests. Lastly, there is evidence of teachers’ awareness of the issues surrounding these testing practices. The shared concern about the effectiveness of current practices, along with the expressed need for further training, underscore the importance of developing targeted professional development programs to better prepare teachers in this area.